Rotating Hinge Knee Arthroplasty for Revision Prosthetic-Knee Infection: Good Functional Outcomes but a Crucial Need for Superinfection Prevention - Bourbotte-Salmon, Florian; Ferry, Tristan; Cardinale, Mickaël; Servien, Elvire; Rongieras, Frédéric; Fessy, Michel-Henry; Bertani, Antoine; Laurent, Frédéric; Buffe-Lidove, Margaux; Batailler, Cécile; Lustig, Sébastien; , The Lyon Bone and Joint Infections Study Group (Frontiers in Surgery, 2021)
Introduction: Management of chronic infection following total knee arthroplasty (TKA) is challenging. Rotating hinged prostheses are used in various indications, including infections. However, mechanical or septic complications’ incidence and risk factors have not been well described in this specific situation. Methods: We performed a retrospective cohort study in our regional reference center including patients from 2009 to 2016 for whom rotating hinged prostheses have been used as revision of a prosthetic knee infection. We only selected patients with at least 2-years of follow-up. Functional evaluation was performed using IKS “knee” and “function” scores. Survival rates were assessed by comparing implant removal risks due to mechanic vs. septic causes, using Cox univariate analysis and Kaplan-Meier curves. Risk factors of implant removal were identified. Risk factors for septic failure, i.e. need for subsequent surgery due to infection, were specifically assessed. Results: Forty-six knees were included. Most patients had satisfying functional outcomes (IKS “knee” score: 70.53; IKS “function” score: 46.53 points; knee flexion: 88.75°). The 2-year overall survival rate was 89% but dropped to 65% after 7 years of follow-up. There was a significant higher risk for failure (i.e. implant removal) for septic causes compared to mechanical ones. Patients with ASA score>1, immunosuppression, or with peripheral arterial diseases seemed to have a higher risk for septic failure. Patients with acute infection as initial clinical presentation, according to Tsukayama classification, had higher risk of failure. Out of the 46 patients included, 19 (41.3%) had at least one infectious event on the surgical knee. Most of them were superinfections (14/19) with new pathogens isolated. Among pathogens responsible for superinfections: (i) cefazolin and gentamicin were both active in 6 of them but failed to prevent the superinfection; (ii) cefazolin and/or gentamicin were not active in 8 patients, leading to alternative systemic and/or local antimicrobial prophylaxis reconsideration. Conclusion: Patients with chronic TKA infection, requiring revision using rotating hinge implant, had good functional outcomes but experienced a high rate of septic failure, mostly due to bacterial superinfection. These patients may need optimal antimicrobial systemic prophylaxis, and innovative approaches to reduce the rate of superinfection.